Implementation of the 3th Pancasila Values in Generation Z in the Digital Era of Students in Ppkn Study Program - Ichwani Siti Utami; Sesti Margo Rahayu; Nurzaman Nurzaman; Alinurdin Alinurdin (Journal of Social Research, 2023)
The purpose of this study was to find out the implementation of the values of the third Pancasila precept in Generation Z in the digital era of Pancasila and Citizenship Education study program students at Pamulang University and to find out the efforts to minimize the impact of the digital era in Generation Z in implementing the values of the third Pancasila precept students of the Pancasila and Citizenship Education study program at Pamulang University. The research approach used is a qualitative approach with a descriptive analysis method. Data collection techniques used are observation, interviews and documentation. The results of the study show that the implementation process of the values of the third precept in generation Z in the digital era by students of the Pancasila and Citizenship Education Study Program has gone quite well, with respect for different ethnicities, religions and also different cultures. However, differences in mindset and the ease with which information can be received about various cultures makes Generation Z prefer foreign cultures to their own. Efforts that can be made to minimize the negative impact of the digital era in implementing the values of the third Pancasila precept can be started from self-awareness regarding the importance of values in the precepts of Indonesian Unity. Another effort that can be made from tertiary institutions, especially the Pancasila and Citizenship Education Study Program, is to conduct socialization, seminars that have a connection with the values of the third precepts of Pancasila.